Analyzing Roles and Conflicts of Triumvirate Ministers in Filling Presidential Vacancies in Indonesia - Silubun, Gabriel Adam; Anechitoae, Constantin (CV. Era Digital Nusantara, 2024)
Abstract: This article examines the constitutional position and legal resolution of disputes surrounding the Triumvirate Minister in Indonesia. The Triumvirate Minister, comprising the Ministers of Foreign Affairs, Home Affairs, and Defence, serves as a temporary substitute for the President and Vice President in case of vacancies. However, ambiguity exists regarding their authority and coordination. Purpose: This study aims to clarify the constitutional position of the Triumvirate Minister and propose legal resolutions for disputes among them. It seeks to address ambiguities in regulations and ensure effective governance in Indonesia's presidential system. Design/Methodology/Approach: The research is a normative juridical approach, analyzing constitutional provisions, laws, and regulations concerning the Triumvirate Minister. Secondary data from legal literature and documents are collected through library research, followed by qualitative analysis to interpret the legal framework. Findings: The Triumvirate Minister plays a crucial role as a temporary presidential substitute but lacks clear regulations defining their authority and coordination. Ambiguities may lead to disputes, necessitating resolution by the Constitutional Court to ensure effective governance and adherence to the Constitution. Originality/value: This study contributes to understanding the Triumvirate Minister's constitutional role and the legal framework surrounding their authority and coordination. It highlights the importance of clear regulations to prevent conflicts and maintain governance stability in Indonesia's presidential system.